An ethical reflection on doctor-patient relationship - Adhikari, N (Journal of Kathmandu Medical College, 2014)
Not available. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10556 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, page: 40